Antibacterial Toxins: Gram-Positive Bacteria Strike Back!. Issue 2 (February 2018) - Jamet, Anne; Charbit, Alain; Nassif, Xavier
Abstract : Bacteria live in communities where strains compete with each other by deploying an arsenal of antibacterial toxins. While the past decade revealed the vast array of antibacterial toxins secreted by Gram-negative bacteria, several recent studies have begun to uncover the ability of Gram-positive bacteria to battle with their own weapons.